Practice of the Muluki Criminal Code in Nepal - Khanal, Bishnu Prasad (KDCBAR Law Journal, 2025)
The Muluki Criminal Code, 2074 is a significant modernization effort, its practice in Nepal is hampered by systemic challenges like judicial delays, resource shortages, investigative weaknesses, and access barriers. The prosecution process in Nepal is a complex legal journey defined by the Cr PC 2074 but significantly hampered in practice by systemic inefficiencies, resource limitations, and access barriers. This gap requires sustained efforts in judicial reform, increased investment in the justice sector, strengthening of institutions, enhanced training, and a greater commitment to protecting the rights of all individuals within the process. Landmark decisions demonstrate the Supreme Court's active role in ensuring the Muluki Criminal Code 2074 is implemented in a manner that upholds constitutional rights, promotes justice, and addresses systemic flaws in Nepal. The Criminal Code, 2074 exactly cannot represent the Nepalese Social Phenomena in current law practice system in Nepal.